A factor converting viable but nonculturable Vibrio cholerae to a culturable state in eukaryotic cells is a human catalase. Issue 4 (13th May 2015) - Senoh, Mitsutoshi; Hamabata, Takashi; Takeda, Yoshifumi
Abstract In our previous work, we demonstrated that viable but nonculturable (VBNC) Vibrio cholerae O1 and O139 were converted to culturable by coculture with eukaryotic cells. Furthermore, we isolated a factor converting VBNC V. cholerae to culturable (FCVC) from a eukaryotic cell line, HT‐29. In this study, we purified FCVC by successive column chromatographies comprising UNO Q‐6 anion exchange, Bio‐Scale CHT2‐1 hydroxyapatite, and Superdex 200 10/300 GL. Homogeneity of the purified FCVC was demonstrated by SDS‐PAGE. Nano‐LC MS/MS analysis showed that the purified FCVC was a human catalase. An experiment of RNAi knockdown of catalase mRNA from HT‐29 cells and treatment of the purified FCVC with a catalase inhibitor, 3‐amino‐1, 2, 4‐triazole confirmed that the FCVC was a catalase. A possible role of the catalase in converting a VBNC V. cholerae to a culturable state in the human intestine is discussed.